2016
DOI: 10.1111/hojo.12160
|View full text |Cite
|
Sign up to set email alerts
|

It's as if you're not in the Jail, as if you're not a Prisoner’: Young Male Offenders’ Experiences of Incarceration, Prison Chaplaincy, Religion and Spirituality in Scotland and Denmark

Abstract: This article explores Scottish and Danish young male offenders’ experiences of incarceration, prison chaplaincy, religion and spirituality. The findings from in‐depth face‐to‐face semi‐structured interviews (n = 15) suggest that although Scotland and Denmark are increasingly secular countries, the prison environment (deprivation of liberty, vulnerability and feelings of guilt) seems to engender pro‐religious/spiritual attitudes and an interest in prison chaplaincy services. Working with interfaith chaplains en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…SP11 acknowledged that this change in identity, by way of spirituality, may never have had chance to take root had he continued to be allowed to offend without incarceration. While SP11 referred to the Bible as acting as a base for his spiritual development, Deuchar et al .’s () comparative study of Scottish and Danish inmates likewise identified a wide range of spirituality and religious practices as significantly aiding the desistance process, in as much that it allowed a moral reconfiguration away from criminal codes to spiritual codes.…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…SP11 acknowledged that this change in identity, by way of spirituality, may never have had chance to take root had he continued to be allowed to offend without incarceration. While SP11 referred to the Bible as acting as a base for his spiritual development, Deuchar et al .’s () comparative study of Scottish and Danish inmates likewise identified a wide range of spirituality and religious practices as significantly aiding the desistance process, in as much that it allowed a moral reconfiguration away from criminal codes to spiritual codes.…”
Section: Results and Analysismentioning
confidence: 99%
“…However, although our data suggested a lack of prison gang culture, we also noted the way in which the young men in our sample continued to be exposed to the ‘prison code’ which prioritised ‘bravado’ and a strong focus on hypermasculinity (Deuchar et al . ). Violent confrontations between former street gang rivals – combined with the competition for recognised status that arose from drug procurement and distribution within the prisons – meant that our interviewees were hindered in their attempts fully to reform.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations